Pengaruh Growth Mindset dan Resiliensi terhadap Learning Agility pada Karyawan Startup Company - Gresika Tabitha Vinesian; Reza Lidia Sari (Universitas Airlangga, 2023)
In a rapidly changing world like today, startups face significant challenges in adapting to technological, economic, and environmental changes to remain competitive in the business world. To enhance their competitive advantage amidst these changes, startups, known for their fast-paced business operations, require employees who can adapt swiftly. This research aims to examine the influence of a growth mindset and resilience on learning agility among employees at a mental health startup company in Surabaya. A cross-sectional survey involving 50 employees was conducted, and the collected data were analyzed using multiple linear regression analysis techniques. The research findings indicate that both a growth mindset and resilience have a positive influence on learning agility. Therefore, startup companies can implement interventions such as training on a growth mindset and resilience to enhance the learning agility of their employees, enabling them to remain competitive in the business industry.